Pembentukan Karakter Religius Melalui Program Gerakan Anak Pejuang Subuh Di TPQ Al Muqorrobin Panjangsari Gombong - Istiqomah, Dini; Husna, Nihayatul (IAINU Kebumen, 2025)
Behind such rapid progress, the negative impact is starting to be seen, namely the decline in the noble values of religion, customs and social norms which so far have been highly respected and considered important by the Indonesian nation and are now starting to be ignored. Seeing these conditions, TPQ Al Muqorrobin Panjangsari Gombong implemented a program called the